Estudo do efeito comportamental e neuroprotetor da Erythrina velutina na isquemia cerebral aguda em camundongos - Rodrigues, Francisca Taciana Sousa (2013)
The study shows the effects of standardized extract of Erythrina velutina (EPEV) in motor activity, in memory and in the determination of amino acids in mice brain undergoing global cerebral ischemia (ISQ). Animals (swiss mice, males, 30-35 g) were subjected to transient cerebral ischemia by occlusion of both carotid arteries during 30 minutes and treated for 5 days with EPEV 200 or 400 mg/kg and Memantine (MEM) 10 mg/kg, 2 or 24 hours after ischemia. The same procedure was done in false-operated group + DMSO (FO) with the exception of clamping the carotid arteries. On day 6 after induction of ischemia, the animals were subjected to tests of locomotor activity, rota rod and memory (step down, Y-maze and object recognition), then were sacrificed and dissected brains on ice the prefrontal cortex (PFC), Hippocampus (HC) and striatum (ST) determination of aspartic acid (ASP), glutamate (GLU), glycine (GLY), taurine (TAU) and gamma-amino-butirico acid (GABA). No change in exploratory activity was detected between the groups vertical FO and ISQ treated with solvents, as well as between the groups treated with EPEV or MEM, however, an increase in exploration activity across (rearing) was observed on EPEV 200 mg 2H group when compared to the ISQ. In rota rod test no substantial modification has been detected between the groups FO and ISQ treated with DMSO and in the groups treated with EPEV and MEM. Memory test step down the ISQ has affected the processes of acquisition and retention of memory both in the immediate phase (recent memory-RM), and the consolidation phase (late memory-LM) when compared with the group FO. Comparing the treatments we observed a significant increase in the length of stay in the non-electrified platform, in the animals treated after ischemia when evaluated in RM, and in LM. Y-maze test the ISQ promoted a retention damage in memory of animals compared to the control group (FO), however the EPEV and MEM managed to revert the damage on the acquisition of memory induced by ISQ at both doses. Animals subjected to ISQ showed deficit in memory also in object recognition test, this deficit was reversed by EPEV 400 mg 2 or 24 H group and by MEM 10 mg. The dosage of amino acids after testing behavior on PFC, HC and ST presented an increase in concentration of excitatory amino acids (ASP, GLU) in animals ISQ + DMSO when compared to FO. In the CPF that increase can be reversed by the animals treated with EPEV 24H at both doses and MEM 10 mg 24H in HC this increase was reversed by all treated groups. In CE there was a reduction in levels of GLU on EPEV 200 mg 2 or 24H and MEM 10 mg 2H. Regarding the levels of GABA, GLY and TAU in the CPF, there was reversal of values in the Group EPEV 200 mg 2H and 400 mg in both treatment schedules as well as group MEM 10 mg 24H when compared to the control that suffered ischemia. In the HC an increase in levels of GLY and TAU can be seen in EPEV 200 mg 24H, EPEV 400 mg 2H and MEM 10 mg 24H groups. GABA levels were already reverted on EPEV 400 mg and MEM 10 mg groups at the time of 24H. The ST presented high levels of TAU and GABA in the ISQ animals when compared with the control. The value of GABA was only reversed by EPEV 200 mg 2H group. With this, we concluded that the EPEV at both doses developed a neuroprotective action, possibly by reducing the levels of excitatory amino acids and inhibitory increase after ischemia.